2013
DOI: 10.3724/sp.j.1005.2013.01189
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function analysis of Arabidopsis thaliana SRO protein family

Abstract: Many biotic and abiotic stresses can cause oxidative stress in plants. The identification of components involved in plant response to oxidative stress has attracted wide attention. The members of AtSRO family, including AtRCD1, AtSRO1, and AtSRO5, regulate plants' response to oxidative stress. AtSROs participate in plant normal growth and development, and play important roles in plant response to stresses, such as drought, salt, heavy metal, and so on. In addition, AtSROs possess some special domains, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Methyl jasmonate can also be used as the core signal factor of plant resistance to insect invasion [26]. Salicylic acid (SA) is an important signaling molecule for plants to cope with biotic or abiotic stress [12]. Gibberellins are phytohormones that regulate multiple developmental processes, such as seed germination, stem elongation, flowering, and fruit development [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methyl jasmonate can also be used as the core signal factor of plant resistance to insect invasion [26]. Salicylic acid (SA) is an important signaling molecule for plants to cope with biotic or abiotic stress [12]. Gibberellins are phytohormones that regulate multiple developmental processes, such as seed germination, stem elongation, flowering, and fruit development [27].…”
Section: Discussionmentioning
confidence: 99%
“…Six known ID of Arabidopsis thaliana SRO genes [12] were put into Arabidopsis genome database (TAIR) [31] to obtain their protein sequences. Using Arabidopsis SRO protein sequences as probes, the candidate members of Chinese cabbage SRO family were searched and the coding sequences (CDS) and amino acid sequences of the B. rapa SRO genes were downloaded from the Brassica database [32].…”
Section: Identification and Sequence Analysis Of Sro Genes In Chinese Cabbagementioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of AtSRO5 could mediate proline metabolism in Arabidopsis mitochondria, thereby improving plant salt stress and antioxidant capacity ( Borsani et al, 2005 ). AtSRO2 , AtSRO3 and AtSRO5 have shown changes in transcript levels in response to light stress, salt treatment and exposure to O 3 ( Jaspers et al, 2010b ; Li et al, 2013 ), but AtSRO4 has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, five homologs (named as AtSRO1-5) of AtRCD1 were also identified in Arabidopsis. AtSRO1 is the closest homolog of AtRCD1, both of them contained WWE domain at the N-terminus and possessed similar expression patterns, but they play unequally redundant and independent roles in certain developmental processes and the response to various stresses [14,[16][17][18]. For example, sro1-1 mutants displayed only unconspicuous morphological phenotypes, while rcd1-3 sro1-1 double mutants showed even more extreme phenotypes than rcd1-3 [13,14].…”
Section: Introductionmentioning
confidence: 99%